Anti-Müllerian hormone as a qualitative marker – or just quantity?. Issue 3 (June 2020) - Kotlyar, Alexander; Seifer, David B.
Abstract : Purpose of review: In this review, we will summarize research looking into anti-Müllerian hormone (AMH) as a measure of oocyte quality. Recent findings: AMH is a key factor involved in embryogenesis but also in the development of early follicles. Owing to its relatively small inter and intracycle variability, it has become a widely used method of ovarian reserve testing. In the realm of assisted reproductive technology, it has demonstrated a reliable ability to gauge the number of oocytes obtained during an in-vitro fertilization cycle. For these purposes, AMH is a readily measured quantitative tool. However, its qualitative role is as yet undefined. Summary: Although levels of this hormone have been associated with fertilization, blastulation, implantation, and clinical pregnancy rates, there is no clear link with live-birth rates. Furthermore, AMH levels do not appear to correspond with risk of fetal trisomy. AMH does show significant predictive value for the risk of premature ovarian insufficiency and time to onset of menopause.